Study the characteristics of the force-time curve and some biomechanical variables for head- scoring skill - Salall, Mohammed Majeed (International Journal of Psychosocial Rehabilitation, 2020)
Introduction and the importance of research, and through it the importance of biomechanics in improving the level of skillful performance of many activities and sports, including the game of football, was discussed in the study of one of the most important skills in the game of football, which is head scoring, which is the end and natural end of investing A method used by the team to win the match, so the researcher decided to study and analyze this skill and find relationships to some of its variables through kinematic and kinematic analysis to bring it to the level of ideal technical performance in order to complete part of the requirements for reaching the mathematical form.This section also included the research problem, which came through the researcher's observation of the lack of studies in the biomechanical field of football in general and in the skill of scoring the head in particular, so there was a need to conduct such a study to know and analyze the kinematic and kinematic variables of the skill of scoring the head under conditions similar to the cases of play As the researcher never knows this skill has been studied in football at the level of the country in biomechanical terms, which necessitated the researcher to delve into this skill to clarify its importance and study it from various mechanical aspects.As for the research objectives, they are as follows: • Identify the nature of the (strength_ time) curve for the skill of scoring the head from jumping in the research sample.• Identify the values and nature of the relationship for some biomechanical variables (Kinetic and Kinematic), some with others, due to the skill of scoring the head from jumping in the research sample.• Identify the nature of the relationship between the values of some kinematic variables with each other and the nature of the relationship between the values of some kinematic variables with each other as well for the skill of scoring the head from the jumping of the research sample.As for the research hypotheses, they were: -• Some of the Kinetic variants of head-scoring skill are related to each other in a significant  • Some of the kinematics variants of head-scoring skill are related to each other in a significant • Some Kinetic variables are related to some kinematic variants of the head scoring skill of jumping with a significant relationship.